Association of factor II G20210A, factor V G1691A and methylenetetrahydrofolate reductase C677T gene polymorphism with different forms of myocardial infarction: ST segment elevation and non-ST segment elevation - Ćućuz JokIć, Milica; Ilić, Vesna; Cikota-Aleksić, Bojana; Obradović, Slobodan; Magić, Zvonko (Vojnosanitetski pregled, 2021)
Background/Aim. Coagulation Factor II G20210A and Factor V G1691A variants are moderately associated with coronary artery disease. Polymorphism of methylenetetrahydrofolate reductase (MTHFR) gene C677T is associated with myocardial infarction (MI) in some ethnical groups. At the present time there are rare studies which try to differentiate two forms of MI, ST-elevation MI (STEMI) and non ST-elevation MI (NSTEMI) according to the genetic background. The aim of the study was investigate the association of polymorphisms of Factor II G20210A, Factor V G1691A and MTHFR C677T with different forms of MI: STEMI and NSTEMI. Methods. The study included 82 patients, divided into two cohorts: patients with STEMI (49 patients) and NSTEMI (33 patients). Genetic factors that would be different in those two entities, included in response to plaque rupture and occlusion of coronary artery, were examined. The peripheral blood lymphocytes were used as DNA source. Genotypes were determined on the polymerase chain reaction (PCR) based methodology. Results. The frequency of MTHFR C677T CT genotype was higher in the patients with NSTEMI in comparison with the patients with STEMI [odds ratio (OR) 3.33; 95% confidence interval (CI) 1.22–9.15; p = 0.02]. Logistic regression analysis shows MTHFR CT genotype as an independent prognostic factor for development of NSTEMI (OR 3.15; 95% CI 1.20–8.29; p = 0.02). There were no differences between two patients groups in frequency of Factor II G20210A and Factor V G1691A gene polymorphism. Conclusion. MTHFR C677T CT genotype was significantly associated with the NSTEMI development examined patients.